The Effect Of Job Satisfaction And Organizational Commitment On The Turnover Intention Of Apparel Store Employee - Moh Sabran Sabran; Andi Musda Mulya (Economy Deposit Journal (E-DJ), 2021)
ABSTRACT This research was conducted to find out the effect of job satisfaction and organizational commitment on the turnover intention of apparel store employee at Bumi Harapan Market in Tolitoli. Research design using Causal Descriptive with primary and secondary data sourcer. The main research instrument is questionnaire and distributed to 36 respondents from 18 apparesl store in this market. Data analysis using descriptive analysis, instrument test using validity and realibility, classis assumption test, multiple linear regression analysis and hypothesis in the form simultan test, partial test and coefficient of determination test. The result of the research show that job satisfaction and organizational commitment simultaneously and significantly affect on the turnover intention of apparel store employee at Bumi Harapan Market in Tolitoli. In other hand for partial, significant and negative only given by organizational commitment. This shows if the employees have high organizational commitment then the employees will have low turnover intention.